Agreement on Academic Cooperation between National University Corporation Kochi University and Universiti Malaysia Sarawak - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak, UNIMAS, 2009)
The purpose of this Agreement is to develop academic and educational cooperation and to promote mutual understanding between the two universities.